2019
DOI: 10.1002/tcr.201800175
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Control in Contorted Aromatic Materials

Abstract: This Account details key developments in dimensional control of contorted aromatics for organic electronics. Coronene, perylene, pyrene, and [4]helicene, which are fragments of graphene, can be contorted using facile synthetic chemistry into large nanoribbons and nano‐architectures. In comparing contorted or higher‐dimensional graphene architectures to planar or lower‐dimensional species, the materials properties are reliably enhanced for the contorted aromatics. Examples of enhanced properties include optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…6 Contorting the molecules allows new types of intermolecular contacts to emerge and in some cases can enhance intermolecular charge transfer. 7 In particular, racemic helicenes have great potential for the growth of single crystals featuring multi-dimensional charge transport. In 2004, Rajca et al reported a racemic single crystal of thia [7] helicene, with the characteristic of two-dimensional charge transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Contorting the molecules allows new types of intermolecular contacts to emerge and in some cases can enhance intermolecular charge transfer. 7 In particular, racemic helicenes have great potential for the growth of single crystals featuring multi-dimensional charge transport. In 2004, Rajca et al reported a racemic single crystal of thia [7] helicene, with the characteristic of two-dimensional charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…7 In particular, racemic helicenes have great potential for the growth of single crystals featuring multi-dimensional charge transport. In 2004, Rajca et al reported a racemic single crystal of thia [7] helicene, with the characteristic of two-dimensional charge transport. 8 In 2015, Itami et al synthesized a double helicene with three-dimensional lamellar packing.…”
Section: Introductionmentioning
confidence: 99%
“…Contorted polycyclic aromatic hydrocarbons (PAHs, or nanographenes) have received considerable attention in the past decades because of their intriguing optoelectronic properties and applications in organic electronics . Among the contorted PAHs, helicenes represent an important class of compounds because of their unique nonplanarity, inherent chirality, and dynamic behavior .…”
Section: Figurementioning
confidence: 99%
“…[45,46] The contorted π-conjugated molecules have been identified as ideal receptors of molecular recognition. [47] The co-assembled structures of these contorted systems with spherical molecules have been very well documented in the literature. [48] Helicenes are one of the best examples of the contorted core.…”
Section: Introductionmentioning
confidence: 96%
“…The literature has reported that the co‐assembly involving curved π‐fused systems and electron‐deficient systems display promising photovoltaic effect [43,44] and OLEDs [45,46] . The contorted π‐conjugated molecules have been identified as ideal receptors of molecular recognition [47] . The co‐assembled structures of these contorted systems with spherical molecules have been very well documented in the literature [48] .…”
Section: Introductionmentioning
confidence: 98%